Ayurvedic Management of Adenomyosis in the Purview of Vataja Asrigdara: A Case Study - Dr. Rachana Madhukar; Prof. (Dr.) Manjusha Karkare (The Bioscan, 2026)
Background: Adenomyosis is a benign uterine disorder characterized by heavy menstrual bleeding, dysmenorrhea, and chronic pelvic pain, significantly affecting quality of life in multiparous women. In Ayurveda, a similar clinical presentation is described under Vātaja Asṛgdara, a subtype of Asṛgdara resulting from vitiation of Vāta and Rakta. Objective: To evaluate the effectiveness of classical Ayurvedic management in a case clinically diagnosed as adenomyosis and interpreted as Vātaja Asṛgdara